Genetic and Genomic Resources for Grain Cereals Improvement 2016
DOI: 10.1016/b978-0-12-802000-5.00007-1
|View full text |Cite
|
Sign up to set email alerts
|

Finger and foxtail millets

Abstract: No part of this publication may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Details on how to seek permission, further information about the Publisher's permissions policies and our arrangements with organizations such as the Copyright Clearance Center and the Copyright Licensing Agency, can be found at our website: www.elsevier.com/permis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…The major collections of foxtail millet germplasm are conserved in China, India, France, and Japan, while India and African countries such as Kenya, Ethiopia, Uganda, and Zambia have major finger millet collections. Similarly, the major collections of proso millet germplasm are in the Russia, China, Ukraine, and India; barnyard millet in Japan and India; kodo millet in India and USA; and little millet in India [171,175]. Major collections of teff, fonio and job's tears were conserved in Ethiopia, USA and Japan, respectively.…”
Section: Global Status Of Germplasm Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The major collections of foxtail millet germplasm are conserved in China, India, France, and Japan, while India and African countries such as Kenya, Ethiopia, Uganda, and Zambia have major finger millet collections. Similarly, the major collections of proso millet germplasm are in the Russia, China, Ukraine, and India; barnyard millet in Japan and India; kodo millet in India and USA; and little millet in India [171,175]. Major collections of teff, fonio and job's tears were conserved in Ethiopia, USA and Japan, respectively.…”
Section: Global Status Of Germplasm Resourcesmentioning
confidence: 99%
“…Ramakrishnan et al [141] identified finger millet mini core accessions tolerant to low phosphorus stress; five (IE 5201, IE 2871, IE 7320, IE 2034, IE 3391) of them had high root and shoot length, root hair density, and root hair length. A limited number of resistant sources for major diseases, and to some extent, for pests in proso, barnyard, little and kodo millets have been reported [171,175]. In teff, shoot fly is an important insect pests.…”
Section: Germplasm Diversity Representative Subsetsmentioning
confidence: 99%
“…Of this, pearl millet constitutes the vast majority of germplasm represented by 23,092 accessions including landraces, cultivars, genetic stocks, breeding lines, and wild relatives (Upadhyaya et al, 2016a). Finger millet germplasm consisting of 6,084 accessions is grouped under two subspecies, africana and coracana on the basis of morphology of inflorescence (Vetriventhan et al, 2016). Foxtail millet is a self-fertilizing species including 1,542 accessions from 23 different countries.…”
Section: Characterization Of Millet Germplasm For Grain Nutrientsmentioning
confidence: 99%
“…Foxtail millet is a self-fertilizing species including 1,542 accessions from 23 different countries. Foxtail millet accessions are classified into three races, namely indica, maxima , and moharia and 10 subraces (Vetriventhan et al, 2016). Barnyard millet germplasm comprises of 749 accessions mainly from Japan and India (Upadhyaya et al, 2016c).…”
Section: Characterization Of Millet Germplasm For Grain Nutrientsmentioning
confidence: 99%
“…Finger millet straw is used as forage for cattle, sheep, and goats. In Uganda, the byproducts of finger millet beer production are fed to chickens, pigs, and other animals (Vetriventhan et al, 2016). It is an ideal food for expectant women, breast-feeding mothers, children, the sick, and diabetics (National Research Council, 1996).…”
mentioning
confidence: 99%